A Health Technology Assessment Based on Chinese Guideline: Active Vitamin D and Its Analogs in the Treatment of Osteoporosis - Huang S; Li J; Hu X; Chen J (Dove Medical Press, 2024)
Siyong Huang, Jiabao Li, Xiao Hu, Jisheng Chen Key Specialty of Clinical Pharmacy, The First Affiliated Hospital of Guangdong Pharmaceutical University, Guangzhou, People's Republic of ChinaCorrespondence: Jisheng Chen, Key Specialty of Clinical Pharmacy, The First Affiliated Hospital of Guangdong Pharmaceutical University, Guangdong, 510080, People's Republic of China, Tel +86 20-87622305, Fax +86 20-61321967, Email cjslym@163.comObjective: To quantitatively assess all dosage forms of three active vitamin D and its analogs, namely, calcitriol, alfacalcidol, and eldecalcitol, to provide a basis for the selection of active vitamin D and its analogs in hospitals.Methods: In this study, three active vitamin D and its analogs were evaluated by quantitative scoring in five dimensions, including pharmaceutical properties (28 points), efficacy (27 points), safety (25 points), economy (10 points), and other attributes (10 points).Results: The final scores of quantitative assessment for the selection of alfacalcidol soft capsules, calcitriol soft capsules I, calcitriol soft capsules II, alfacalcidol tablets, alfacalcidol capsules, alfacalcidol oral drops, calcitriol injection, and eldecalcitol soft capsules were 73.17, 72.06, 71.52, 71.29, 69.62, 68.86, 65.60, 64.05 points.Conclusion: Based on the scoring results, alfacalcidol soft capsules, calcitriol soft capsules I, calcitriol soft capsules II, alfacalcidol tablets can be entered into the medication list of medical institutions as strongly recommended drugs. This study offers guidance on selecting and using active vitamin D and its analogs in hospitals, with consideration for the patient's needs. Keywords: osteoporosis, active vitamin D, calcitriol, alfacalcidol, eldecalcitol, hospital health technology assessment